Morphological Changes and Ionic Regulations in Gills of Euryhaline Fish during Osmoregulation: A Review - Surendran , Surya; Ampili , M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Euryhaline fish can thrive in both freshwater habitat and saltwater conditions. The migration from one salinity range to another involves the use of various organs like gills, kidneys and intestine which are all osmoregulatory in function. Among them, gills are considered to be the most important osmoregulatory organ with multiple functions and various ion transporters which helps the fish to survive the adverse environmental conditions. The gills have various cells involved in osmoregulation and mainly the MR (Mitochondria Rich) cells which have many transporters for intake and excretion of ions according to the environmental salinity. This review briefs the studies of various researchers on the morphological changes and the ionic variations in the fish gills which helps in acclimating them to different salinities.